PERAN DIKMAS LANTAS DALAM MENCEGAH PELANGGARAN LALU LINTAS YANG DILAKUKAN OLEH PELAJAR SMA DI WILAYAH HUKUM POLRES KARAWANG - Muhammad Rifky Santosa (Police Studies Review, 2017)
tes Environmental safety is a very important aspect for the community in carrying out its activities. Security and public order is one of the main tasks of the National Police as Article 13 of Law Number 2 of 2002. The existence of social dynamics in the community requires Polri to take preventative or preemptive measures against traffic violators. As the successor to the nation, students are the ones who must be instilled learning especially regarding traffic order and security. Dikmas Lantas is a preventive program carried out by the Traffic Unit Unit for the violation of traffic. This is intended to foster student awareness and as an education not to violate traffic. Therefore, a study was conducted which aimed to find out the picture of student traffic violations, the role of Dikmas then by the Unit in charge, and the factors that influenced Dikmas Lantas. This thesis research is a research with a qualitative approach. A qualitative approach is the process of understanding a problem based on detailed informant views. This type of research is analytical descriptive, to give a detailed description. The sources of this research data are primary data sources and secondary data sources. Then, the data collection techniques used in writing this thesis are observation, interview, and document study. Furthermore, to test the accuracy and accuracy of the data in this study using tringulation techniques. Data analysis techniques in qualitative research are data reduction, data presentation, and drawing conclusions. The results showed that the Dikmas Lantas activities carried out by the Dikyasa Unit in preventing traffic violations had proceeded only that there were a number of obstacles found including the lack of number of Dikyasa Unit personnel according to Perkap No. 23 of 2010 and the implementation of the program which was not evenly distributed to students in Karawang Regency, so there needs to be innovation improvements so that the Dikmas Lantas activities can run better in the future.